ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT. PELABUHAN INDONESIA IV (PERSERO) CABANG SAMARINDA - -, Siti Asiyah (EKONOMIA, 2019)
PT. Pelabuhan Indonesia IV (Persero) Branch Samarinda 2014-2016 period is measured by the Likuditas Ratio in terms of Current Ratio. 2) financial performance of PT. Pelabuhan Indonesia IV (Persero) Branch Samarinda in the 2014-2016 period is measured by the Solvency Ratio in terms of Debt to Asset Ratio. Financial performance of PT. Pelabuhan Indonesia IV (Persero) Branch Samarinda in the 2014-2016 period is measured by the Profitability Ratio in terms of the Net Profit Margin.The theory of this research is financial management that focuses on financial statment analysis, using three ratio ratios, solvency ratios and profitability ratos. Each ratio is taken by one variable, namely Current Ratio for Liquidity ratio, Debt to Asset Ratio for solvency ratio and Net Profit Margin for profitability ratio. The analytical tool used is the liquidity ratio in terms of Current Ratio. Solvency ratio which is viewed from Debt to Asset Ratio. And profitability ratios are reviewed from Net Profit Margin.The results of the study show : 1) Current Ratio has increased in 2015 and there was a decline in 2016 the decline was due to reduced assets of the company so that liquidity decreased very sharply. 2) Debt to Asset Ratio has decreased in 2015 and has increased in 2015, the increase in corporate performance has decreased with the increasing portion of debt in asset funding, 3) Net Profit Margin has decreased in the period 2014 to 2016 due to net income after income tax increases, which is greater than operating income.